Public Private Partnership for Sustainable Tourism in Oman - Al-Azri, Abdullah Khalfan; Ramachandran, Nithya; Jetti, Edukondala Rao (Journal of Ecohumanism, 2024)
The aim of this research is to explore the role of Public-Private Partnerships (PPPs) in promoting sustainable tourism development in the Sultanate of Oman, emphasizing on their significance in terms of pooling of knowledge and capital, building the needed tourism infrastructure, safeguarding the ecosystem, heritage and the country’s rich culture and traditions, etc. The study employed a quantitative research methodology to evaluate the effectiveness of PPPs in fostering sustainable tourism in Oman. A survey was administered using a structure questionnaire to assess the alignment of PPPs with Oman’s sustainable tourism initiatives. Using snowball sampling, data was collected from 35 key stakeholders involved in sustainable tourism in Oman. Multiple regression analysis was employed using SPSS software to study the impact of PPPs on sustainable tourism. The study affirmed that PPPs would ensure pooling of knowledge and environmental protection thereby having significant impact on tourism development in Oman, while the influence of PPPs on infrastructure development and capital accumulation for tourism growth is found to be negligible. The study revealed that stable political environment, prudent governance and social/community support to be the critical success factors for strengthening PPPs while emphasizing on the need for effective risk management practices and accurate cost-benefit analysis to further strengthen the partnership between the two sectors. The study concludes by offering both theoretical and practical implications to the policymakers and industry leaders for positioning Oman as one of the preferred global tourism destinations.